Pengaruh Pembelajaran Discovery Learning Terhadap Kemandirian Belajar Dan Pemahaman Siswa Pada Materi Akuntansi Kelas X Di Smkn 1 Kamal - Purwantiningsih, Anis Tri; Tri Eka Silver, Soesiana; Muhajir (Penerbit STKIP PGRI Bangkalan, 2024)
This study was conducted to determine effect of discovery learning model on learning independence and student understanding of basic accounting equation material in class X accounting and finance at SMKN 1 Kamal. Study used quantitative assessment with questionnaire research instruments and test questions. Using population 49 students with samples, class X AKL-1 (24 students), class X AKL-2 (23 students). Sampling using nonprobability sampling method with saturated sampling technique. Data processing uses IBM SPSS v.21 for windows application with analysis method of validity test, homogeneity test, normality test, independent sample T-test test and, multivariate analysis of variance test or manova test. Testing independent sample T-test test, data obtained first hypothesis sig value. 0.003 <0.05, meaning effect discovery learning model on learning independence in basic accounting equations lesson of class X AKL SMKN 1 Kamal students, second hypothesis obtained data sig value. 0.000 <0.05, meaning effect discovery learning model on student understanding of basic accounting equations in class X AKL students of SMKN 1 Kamal. Last result, multivariate analysis of variance (Manova) test obtained sig value data. 0.000 <0.05, meaning effect discovery learning model on learning independence and student understanding in basic accounting equation class X AKL SMKN 1 Kamal. Conclusion, there is effect of discovery learning model on students' understanding in basic accounting equation subject of class X AKL SMKN 1 Kamal. Learning using discovery learning model is considered effective in increasing students' learning independence and understanding in basic accounting equation subject of class X accounting and finance of SMKN 1 Kamal